2013
DOI: 10.4081/mrm.2013.541
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance in COPD patients followed in a real practice

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is an important public health issue in many countries which is estimated to become the fifth cause of disability and the third cause of mortality in the world within 2020. The objective of this study was to identify the clinical characteristics in the real clinical practice of a sample of patients with COPD followed in a pulmonology clinic. Methods: The initial sample contained 207 subjects with respiratory claims that searched for specialized treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…While all COPD symptoms can predict long-term treatment response, breathlessness (dyspnoea) is one of the best predictors [6]. Dyspnoea is a cardinal feature and the key symptom of COPD, causing distress that contributes significantly to the disease burden [7][8][9]. Dyspnoea grade is closely linked to exacerbation risk [9], and severity of dyspnoea is also a significant predictor of mortality [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While all COPD symptoms can predict long-term treatment response, breathlessness (dyspnoea) is one of the best predictors [6]. Dyspnoea is a cardinal feature and the key symptom of COPD, causing distress that contributes significantly to the disease burden [7][8][9]. Dyspnoea grade is closely linked to exacerbation risk [9], and severity of dyspnoea is also a significant predictor of mortality [7].…”
Section: Introductionmentioning
confidence: 99%
“…Dyspnoea grade is closely linked to exacerbation risk [9], and severity of dyspnoea is also a significant predictor of mortality [7]. Consequently, as dyspnoea severity increases, so do the healthcare costs of managing patients with COPD [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…6MWT was the most commonly reported measure of exercise capacity (14,15,17,18,20,22,25,26). Based on a minimal clinically important difference (MCID) of 30 metres (32) the 22 metre 6MWT improvement with unsupervised exercise cannot be considered clinically meaningful for people with COPD.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…However, the magnitude of effect did not meet the threshold of 30m for clinically important improvement (30). Four further trials reported 6MWT as an outcome (14)(15)(16)20) in a COPD population but data could not be obtained from one study (16) and in another three studies (14,15,20) data could only be retrieved from previous systematic reviews (1,30,31). Extraction of trial data from previous reviews is not a widely accepted approach but analysis with the additional three studies is provided in the supplementary material (Figure S1).…”
Section: Exercise Capacitymentioning
confidence: 99%